Wind‐driven upwelling in lakes destabilizes thermal regimes of downstream rivers. (31st December 2014) - Lisi, Peter J.; Schindler, Daniel E.
Abstract Natural lakes are generally assumed to stabilize thermal regimes of downstream rivers. This conceptual model does not account for the potential destabilizing effects that wind has on the surface temperatures of thermally stratified lakes and, therefore, on thermal regimes of outflowing rivers. We examined the thermal variation in streams and rivers from 24 watersheds without lakes and 15 draining lakes that varied in surface area (0.3–101 km2) and thus, their potential exposure to wind. Rivers draining large lakes (> 10 km2 surface area) had summer thermal regimes with 1.8 times more variation (expressed as the coefficient of variation) than both rivers draining smaller lakes and watersheds lacking lakes. Statistical decomposition of thermal regimes revealed that ∼ 3% (range: 1–5%) of the thermal variability in rivers below large lakes was from diel‐scale variation, compared to 31% (14–48%) in streams lacking lakes and 24% (6–34%) in those draining smaller lakes. Instead, rivers downstream of large lakes had distinct summer thermal regimes characterized by abrupt cooling events involving drops in temperature of 5–10°C that lasted 1–3 d. These events were generally synchronous across space and not observed in watersheds without lakes or in watersheds draining small lakes. Cooling events in rivers were coordinated with high velocity winds that passed thresholds for upwelling of cool hypolimnetic water to lake outlets. Wind driven upwelling may be a common source of thermal variation in rivers draining large stratified lakes and reservoirs, making them more thermally variable than previously appreciated. The ecological responses to this thermal instability remain unexplored.